Low-Pressure Small MEMS Accelerometer Using Sigma-Delta Modulation - Vasco Lima; Jorge Cabral; Burkhard Kuhlmann; Luis Alexandre Rocha (Proceedings, 2018)
Encapsulation of MEMS accelerometers in vacuum is advantageous, since it allows integration with other sensors, leading to size and cost reduction. One technique to operate MEMS accelerometers in vacuum is the use of closed-loop Sigma-Delta modulation, which has many advantages. In this paper, the design of a vacuum encapsulated small size MEMS accelerometer (0.2 mm2) and the preliminary measured results are presented. Experimental devices were fabricated and operated in 2nd and 3rd order Sigma-Delta modulators, achieving a noise figure of 389 µg/√Hz for a bandwidth of 200 Hz and a measurement range of at least ±1 g.